2020
DOI: 10.1111/phn.12698
|View full text |Cite
|
Sign up to set email alerts
|

Health education interventions for older adults with hypertension: A systematic review and meta‐analysis

Abstract: Objective The study aimed to evaluate the effectiveness of health education intervention for the control of blood pressure (BP) in older adults with hypertension. Methods Five databases were searched in March 2018 for randomized controlled trials to manage hypertension in older adults by health education. The primary outcomes were changes in systolic and diastolic BP. RevMan5 was used for meta‐analysis. Results Seven articles with 1,105 participants were included. In them, 393 (35.56%) older adults participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
14
0
5
Order By: Relevance
“…It also reminds us of an innovative method for health education of older adults with CNCDs. Although there are multiple modalities to conduct health education, the effectiveness among older adults is mixed [ 33 ]. ICT can intensify memory and help with the retention of information through visual, auditory and tactile stimuli [ 34 ], and it is critically important to consider older adults’ individual demands to prompt changes in their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It also reminds us of an innovative method for health education of older adults with CNCDs. Although there are multiple modalities to conduct health education, the effectiveness among older adults is mixed [ 33 ]. ICT can intensify memory and help with the retention of information through visual, auditory and tactile stimuli [ 34 ], and it is critically important to consider older adults’ individual demands to prompt changes in their behavior.…”
Section: Discussionmentioning
confidence: 99%
“…While studies reporting the positive effect of health education on health behavior are prevalent in older people. [30][31][32]57,58 Other research suggests younger adults on prolonged health education interventions are more prone to adopt healthier lifestyles. 59 While supportive methods (i.e.…”
Section: Pt 6 -F; Neet Group: "I Would Honestly Ignore You (If You To...mentioning
confidence: 99%
“…In South Africa between 1998 and 2016, hypertension rates in young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) years) more than doubled calling for preventive interventions. However, with many youth unemployed, young adults struggle to prioritize health or implement healthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the hypertension education manual was developed at the international level (WHO Regional Office for the Western Pacific, 2017). Although an educational intervention could improve BP significantly among older adults with hypertension (OAwHTN), a wide variety of study durations, frequencies, and durations of each education session have been reported (Chen et al, 2020). The integration of supportive interventions into educational interventions has also been suggested.…”
Section: Introductionmentioning
confidence: 99%